2020
DOI: 10.5603/ep.a2019.0044
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-like peptides and ghrelin mitigation of bariatric results depends on obesity level

Abstract: Introduction: Bariatric surgery, as the only effective treatment of obesity, has strong effects on the metabolism, and nervous and endocrine systems. Thus, based on the different opinions about the efficaciousness of morbid obesity treatments, the aim of the present study was to estimate the association of serum ghrelin and Met-enkephalin (native, five amino acids and cryptic, precursor of enkephalin) concentrations with body mass index (BMI) value in bariatric patients within 30 postoperative days. Material a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Moreover, the mRNA expression of PENK was increased by more than 90% after naltrexone injection, which may suggest the Interestingly, naltrexone affected also ghrelin secretion or/and synthesis in the duodenum increasing its concentration almost by 61%. Interaction of opioids and ghrelin was found in lamb, piglet (Pierzchała-Koziec, 2012) and human (Dyaczyński et al, 2020). It can be speculated that endogenous opioids in the gut may have a local modulating effect on the ghrelin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mRNA expression of PENK was increased by more than 90% after naltrexone injection, which may suggest the Interestingly, naltrexone affected also ghrelin secretion or/and synthesis in the duodenum increasing its concentration almost by 61%. Interaction of opioids and ghrelin was found in lamb, piglet (Pierzchała-Koziec, 2012) and human (Dyaczyński et al, 2020). It can be speculated that endogenous opioids in the gut may have a local modulating effect on the ghrelin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, adipose tissue releasing cytokines may lead to vasodilation and more permeable blood vessels in thyroid 21 Another explanation that has been suggested is the accumulation of adipose tissue in thyroid gland. 21 In this study, serum TSH was significantly higher in patients with BMI > 25 kg/m 2 than in patients with BMI < 25 kg/m 2 . This finding is consistent with other numerous prior studies that have reported higher blood levels of TSH in obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, adipose tissue releasing cytokines may lead to vasodilation and more permeable blood vessels in thyroid 21 Another explanation that has been suggested is the accumulation of adipose tissue in thyroid gland. 21…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the treatments currently used for obesity is bariatric surgery. However, this method is stressful for the patient, interfering with the homeostasis of the organism by affecting gastrointestinal hormone levels [2]; therefore the search for less invasive methods of treatment appears to be a future direction of research on obesity. Along with obesity-related disease, there often occurs a condition of reduced tissue sensitivity to insulin called insulin resistance.…”
Section: Introductionmentioning
confidence: 99%